Deer hunting - Smith, Richard P., 1949- (Stackpole Books, 2011)
Drawing on up-to-the-minute research and a lifetime of hunting experience, author Richard P. Smith covers the basics and beyond for hunting whitetails and mule deer. -- from publisher's description.